Efectos de la lactancia materna por más de 24 meses: una revisión sistemática. (FABICIB, 2025)
From this review it was possible to visualize a marked benefit on maternal health in all the aspects analyzed, the increase in the duration of breastfeeding has protective effects on bone health, metabolic cardio, joint health and on gynecological conditions, compared to women who they never breastfed, as well as those who breastfed for less time.Most of the studies analyzed indicated a dose-response relationship between breastfeeding and the health benefits for children.In relation to the evidence on the subject studied, there are no contraindications that involve suspending breastfeeding to avoid effects that threaten physical and emotional Breastfeeding is considered an important practice to promote infant health.The evidence of the benefits of breastfeeding has led to it being recommended exclusively for six months, and from that age in conjunction with the introduction of appropriate safe foods and continuing it until two years or more.The objective of this work is to analyze the effects of breastfeeding for more than 24 months on maternal and child health.The justification for this search is based on the existing rejection by both society and health professionals to the practice of breastfeeding for more than 24 months, despite the fact that various international organizations such as WHO or UNICEF advocate for continuity of the same and consider that weaning should occur when the mother and child wish. The fact that there is no way to define in words, breastfeeding that lasts for more than 24 months, is also a personal motivation to do this work.This work was carried out on the basis of a systematic search that included a review of the scientific publications found on this topic.Regarding the effects on maternal health, several large studies included in this review suggest that cumulative breastfeeding for more than 24 months is associated with better cardio-metabolic health. Joint health benefits were found by reducing the risk of development and positive effects on the reduction of gynecological conditions and type 2 diabetes among women, as well as glucose metabolic biomarkers. With regard to bone health, the results found were uneven.Regarding child health, breastfeeding for more than 24 months has a relevant impact on the development of overweight and obesity.Some authors found associations between breastfeeding beyond two years of age and infant development in relation to receptive language and verbal and non-verbal intelligence, visual reception, and motor control performance.The relationship between oral health and breastfeeding remains in dispute; the study included in this review found that breastfeeding for 24 months or more was associated with infant caries.health, reaffirming the recommendation of WHO and UNICEF and that accompany the Argentine Society of Pediatrics and the Latin American Association of Pediatrics of continue breastfeeding for 2 years and more.